La pensée de Gorz : un modèle social et politique possible dans et en dehors de l’école à l’ère du changement climatique ? - Céline Chauvigné (Éducation et Socialisation)
André Gorz (1923-2007) was a philosopher and innovative thinker who criticized capitalist society and founded political ecology. Through his radical thinking, he proposed ways of defending "the lived world" in the face of the climate catastrophe that has been raging since the 1960s. How can this avant-garde figure inspire young people in and out of school to think about, preserve and imagine life on Earth today? From Gorzian models to youth practices, what conditions of possibility can we foresee for meeting contemporary challenges and collective life on Earth?